SELECTION OF PARENTAL COMPONENTS OF SWEET PEPPER HYBRIDS FOR STEPPE AND DRY STEPPE - E. A. Kozlovskaya (Ovoŝi Rossii, 2019)
The main direction in the selection of sweet peppers is the creation of hybrids with a high heterosis effect. The question of components choice for the greatest effect in crossings is studied by breeders and geneticists  of many countries for a long time. However, until now it has not been possible to create a theory that allows breeders conducting practical work to consciously and  reliably choose pairs that  would  provide maxi-mum and stable yield and product quality, depending on the purpose of the variety. In the work various principles of the selection of pairs were used: ecological-geographical, according to the components of attributes  and selection of the maternal form. Using these methods, more than 300 combinations of crosses were obtained.  It is shown that the combination of two ecologically  different parental components of different origin - the local sample and the introduced one - leads to an increase in the heterosis  effect. The best hybrid combinations  with a complex of economically  valuable traits are obtained by crossing local varieties with selected breeding lines. When selecting pairs according to the components of the signs, where local or introduced samples with a different set of features were taken as parental forms, productivity was at the level of the standard. In most cases, when used as the maternal  form of the local variety, the productivity  of the hybrids was  significantly higher compared to  the  reverse crossing. As a result of our studies, it is once again confirmed and proved that the more differences in the places of cultivation and reproduction of parental components, the higher the heterosis effect and the effect of the maternal component is much higher.